Intrinsic ZnO/Al-doped ZnO Homojunction: Structural and Optical Properties - A.S. Ismail; M.H. Mamat; M.F. Malek; M.M. Yusoff; N.D. Md. Sin; S.S. Shariffudin; A.S. Zoolfakar; A.B. Suriani; M.K. Ahmad; I. B. Shameem Banu; M. Rusop (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Intrinsic zinc oxide (ZnO)/Al-doped ZnO (AZO) homojunction film was prepared using two-step immersion processes. The film was characterized using field emission scanning electron microscopy, X-ray diffraction (XRD), Raman spectroscopy, and ultraviolet–visible spectrophotometer to investigate their structural and optical properties. The surface morphology image displays that the ZnO deposited on the nanorod surfaces in layer form with average diameter of nanorods about 95 nm. The structural properties of XRD pattern demonstrate that the film possessed good crystallinity with the preferred orientation at (002) plane. The film also possessed excellent absorption in the ultraviolet (UV) region with optical band gap energy of 3.22 eV. These results indicate that the film has a good potential for optical-based device such a UV sensor.